Chicken Big - Graves, Keith (San Francisco : Chronicle Books, 2010)
A giant chicken hatches from an enormous egg, but the other chickens cannot accept that he is one of them.
Keywords: Chickens -- Juvenile fiction; Size -- Fiction; Humorous stories; Children's stories -- Pictorial works; Chickens -- Pictorial works -- Juvenile fiction; Body size -- Pictorial works -- Juvenile fiction